Government Policy and Ethnic Pluralism in Multiculturalism Space: A Study of Pohuwato District - Sastrowantu, Sastro Wantu (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
Research this explains construction power integration ethnic through local government policy Pohuwato supported by kohesivitas community formulated in unity in diversity and attitude multiculturalism. This research uses the method a qualitative approach for the purpose explore and analyze harmony social of various ethnic that is community and government regulation in managing relations ethnic in Pohuwato regency by using research instruments based on data, the facts and the concept of relevant. This research was intended to look at sorting society by the primordial to break issues related to integration ethnic where the ethnic bound off one another .In addition local policies reached by various ways among other: (1) controlling the relationship between ethnic and construction model the community gorontalo as important element socially, cultural and political famous openly and tolerant; (2) use public space a deliberative so that happened harmonisation conducive between public (community) with the government in protect pluralism the community.